Percepções de uma equipe de saúde acerca da inserção da detecção de risco psíquico e encaminhamento para intervenção precoce na puericultura - Schumacher, Carolina (2017)
Psychology, especially the works related to the Freudo-Lacanian psychoanalytic field, have contributed to the care of infants based on the proposition of the Child Development Risk Indicators (IRDI) and the PREAUT signs, whose main objective is the early detection of psychicogical risk. The use of these indicators and signals is, however, more linked to research groups of the baby clinic than properly inserted in the health system in a broader way. One of the issues that emerges when we think of its introduction for routine use in childcare refers to how the referral for early intervention of infants will be given when it is indicated on the basis of the evaluations carried out. Thus, the objective of this study was to analyze the professionals' perceptions regarding the evaluation and referral processes for the early intervention with the cases of psychicological risk, evaluated through the IRDI protocol and PREAUT signals, as well as to discuss elements for the insertion of these protocols in health system. For this, a study was conducted through interviews with an interdisciplinary health team that has used these protocols in the follow-up of babies from one to twenty four months of age in a research project and who experienced the need for referral of infants with psychicological risk. The results indicate the continuous training and support of an interdisciplinary team are important elements to carry out the process of early detection in an appropriate way. This process requires sensitive listening through continued contact with infants and their families since the IRDI protocol and the PREAUT Signals demand an understanding of the interactions between the baby and his caregivers. The performance of the Psychology professional is fundamental both in the sensitive listening of the baby’s family, and in listening to the interdisciplinary team. The research suggests that the willingness of professionals to listen is the way to capture the family for adherence to early intervention.